2019
DOI: 10.3390/ijerph16214058
|View full text |Cite
|
Sign up to set email alerts
|

A WeChat-Based Self-Management Intervention for Community Middle-Aged and Elderly Adults with Hypertension in Guangzhou, China: A Cluster-Randomized Controlled Trial

Abstract: This study aimed to assess whether a WeChat-based self-management intervention would be effective for community middle-aged and elderly adults with hypertension in Guangzhou, China. We conducted a cluster-randomized control trial with a total of 464 participants (intervention, n = 186; control, n = 276) between March 2018 and May 2019. The self-management intervention lasted for 6 months, consisting of health education, health promotion, group chat, and blood pressure (BP) monitoring. All individuals in the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
2
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(108 citation statements)
references
References 31 publications
3
90
2
13
Order By: Relevance
“…They contain information about weight control, increase physical activity, healthy eating, dietary sodium reduction, smoke abatement and set limit to alcohol. This approach was supported by previous study which used a WeChat-based lifestyle modi cation in China and showed signi cant reduction in blood pressure for patients with hypertension [30] .…”
Section: Lifestyle Modi Cationsupporting
confidence: 66%
“…They contain information about weight control, increase physical activity, healthy eating, dietary sodium reduction, smoke abatement and set limit to alcohol. This approach was supported by previous study which used a WeChat-based lifestyle modi cation in China and showed signi cant reduction in blood pressure for patients with hypertension [30] .…”
Section: Lifestyle Modi Cationsupporting
confidence: 66%
“…It is necessary to initiate research to identify if the additive effect exists in the combination of different methods of patient education for HTN control. Because sending the electronic educational material over the cell phone [ 13 ] is a popular, effective, and economically new method for HTN management based on recent publications, we therefore have initiated a randomized control study to compare the traditional doctor's face-to-face education as the control arm and its combination of the electronic educational material through WeChat and message over the cell phone as the intervention arm. It was planned to include a control arm without any education which was, however, denied by the ethic committee.…”
Section: Discussionmentioning
confidence: 99%
“…Patient education is a common effective nonmedication therapy for HTN [ 2 ]. There are many methods of patient education effective for HTN, such as the traditional doctor's face-to-face education [ 3 ], pharmacist education [ 4 ], nurse teaching session [ 5 ], interdisciplinary education program [ 6 ], educational booklet [ 7 ], group patient education [ 8 ], telephone follow-up education [ 9 ], tailored educational program to change behaviors [ 10 ], and modern electronic methods including the educational e-mail [ 11 ], Facebook advertisement [ 12 ], message and WeChat over the cell phone [ 13 ], and educational Internet platform [ 14 ]. Can we apply many educational methods to boost the effectiveness?…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for most village doctors with lower education level, apart from routine inservice trainings, instant training that had good feasibility and accessibility and was not subjects to venue and time constraint needs to be enhanced. A number of studies had explored the effect of WeChatbased training on others health disorders, such as mental health or chronic cardiovascular and cerebrovascular diseases [13,23]. Our research took TB as an entry point, which may be a good attempt to provide new insights for further improving rural doctors' knowledge of other infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…WeChat users could obtain information and browse resources from all kinds of WeChat platforms easily. WeChat-based training combining with synchronous communication, video, picture, and article were widely used because of its feasibility, acceptability and e cacy [13][14]. The current study aimed to explore the effect of WeChat-based training program on improving the knowledge of TB management for village doctors through a pre-and-post study design.…”
Section: Introductionmentioning
confidence: 99%